The Bicarbonate Transporter (MoAE4) Localized on Both Cytomembrane and Tonoplast Promotes Pathogenesis in Magnaporthe oryzae - Yuejia Dang (MDPI AG, 2021)
Bicarbonate (HCO3−) transporter family including the anion exchanger (AE) group is involved in multiple physiological processes through regulating acid-base homeostasis. HCO3− transporters have been extensively studied in mammals, but fungal homologues of AE are poorly understood. Here, we characterized the AE group member (MoAE4) in Magnaporthe oryzae. MoAE4 exhibits more sequence and structure homologies with the reported AE4 and BOR1 proteins. In addition to the common sublocalization on cytomembrane, MoAE4 also localizes on tonoplast. Yeast complementation verified that MoAE4 rescues boron sensitivity and endows NaHCO3 tolerance in the BOR1 deleted yeast. MoAE4 gene is bicarbonate induced in M. oryzae; and loss of MoAE4 (ΔMoAE4) resulted in mycelial growth inhibited by NaHCO3. Lucigenin fluorescence quenching assay confirmed that ΔMoAE4 accumulated less HCO3− in vacuole and more HCO3− in cytosol, revealing a real role of MoAE4 in bicarbonate transport. ΔMoAE4 was defective in conidiation, appressorium formation, and pathogenicity. More H2O2 was detected to be accumulated in ΔMoAE4 mycelia and infected rice cells. Summarily, our data delineate a cytomembrane and tonoplast located HCO3− transporter, which is required for development and pathogenicity in M. oryzae, and revealing a potential drug target for blast disease control.